Effects of constant and fluctuating saltwater addition on CH4 fluxes and methanogens of a tidal freshwater wetland: A mesocosm study. (31st October 2022) - He, Lulu; She, Chenxin; Huang, Jiafang; Yang, Ping; Yu, Hanxia; Tong, Chuan
Abstract: The importance of salinity in regulating CH4 emissions from coastal tidal wetlands has been widely recognized. However, the different effects of constant versus fluctuating salinity increases on CH4 emission and methanogens in both tidal freshwater marsh and floodplains are not yet well understood. We constructed mesocosm experiments on both a Cyperus malaccensis marsh and an adjacent non-vegetation-covered tidal floodplain over one year. We examined the effects of constant freshwater (CF), constant salinity (CS), and fluctuating salinity (FS) on porewater geochemistry, CH4 flux, methanogen abundance, diversity, and community structure in the tidal marsh and floodplain. Compared with CF treatment, methanogen abundance and Chao1 index were significantly lower in the marsh mesocosms under FS and CS treatment, but only in the floodplain mesocosms under CS treatment. CS treatment significantly reduced the proportion of Methanosarcinales but significantly increased the proportion of Methanobacteriales. Porewater SO4 2− and Cl − concentrations and pH were important factors affecting methanogen abundance and diversity. Both the CS and FS treatments considerably reduced CH4 fluxes in marsh and floodplain mesocosms; the main factor impacting CH4 flux was porewater dissolved CH4 concentration, and both methanogen abundance and Chao1 index were positively correlated with CH4 flux. Our results suggest that both continuous saltwater intrusion caused by sea-level rise and pulse saltwater intrusion perhaps caused by typhoons could reduce CH4 flux from subtropical estuarine tidal freshwater wetlands. Highlights: Addition of constant and fluctuating saltwater (salinity = 10) significantly reduced CH4 emissions from tidal freshwater wetlands. Methanogen abundance, Chao1, and relative abundance of Methanosarcinales significantly decreased with constant saltwater addition. Porewater dissolved CH4 concentrations were important indicators of CH4 fluxes.